Maritime Digital Forensics for Blue Economy Sustainability - Kumar, Rajesh; Kavita, Kavita; Saharan, Meenakshi (Journal of Neonatal Surgery, 2025)
Maritime digital forensics is becoming imperative in protecting marine environments under growing environmental concerns and operational sophistication. This article provides a full review of available forensic technologies—such as extracting data from Voyage Data Recorders (VDRs), Automatic Identification Systems (AIS), and shipboard IoT sensors—and discusses the role of emerging technologies like artificial intelligence for anomaly detection and blockchain for evidence integrity. The review identifies key areas of real-time data integration, scalability, and digital preservation of evidence that hinder adequate environmental protection. Based on these findings, we propose a conceptual framework that unifies digital forensic practices and sustainable maritime operations to encourage incident response, compliance with regulations, and overall stewardship of the environment. While improving marine operation's openness and responsibility towards sustainable development goals, the framework helps to quickly identify and respond to environmental events.